1996
DOI: 10.2307/1192198
|View full text |Cite
|
Sign up to set email alerts
|

Purging the past: The Current State of Lustration Laws in the Former Communist Bloc

Abstract: This article presents a brief overview of the current status of such laws and regulations in the former Communist Bloc. II LUSTRATION LAWS Political partisanship greatly influences the introduction and adoption or failure of lustration legislation. This is apparent in a comparison of countries of the region in which former communists continue to dominate the political

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Mark S. Ellis has demonstrated that lustration laws in Russia, Ukraine and other states that formerly belonged to the former Communist bloc were never enforced and, in fact, were counterbalanced by other laws that made it possible to classify information about individuals who used to work for the Communist Party and the secret police, and who were engaged in operations that could be qualified as crimes against humanity. 160 Gluzman's and van Voren's rejection of the narratives about political psychiatry that are depicted in black and white and their calls to decipher the "shades" of the past and present realities deserve attention. Narratives that exploit a binary concept lack analytical depth.…”
Section: Resultsmentioning
confidence: 99%
“…Mark S. Ellis has demonstrated that lustration laws in Russia, Ukraine and other states that formerly belonged to the former Communist bloc were never enforced and, in fact, were counterbalanced by other laws that made it possible to classify information about individuals who used to work for the Communist Party and the secret police, and who were engaged in operations that could be qualified as crimes against humanity. 160 Gluzman's and van Voren's rejection of the narratives about political psychiatry that are depicted in black and white and their calls to decipher the "shades" of the past and present realities deserve attention. Narratives that exploit a binary concept lack analytical depth.…”
Section: Resultsmentioning
confidence: 99%
“…Th roughout the years of the 1990s it turned out that the Socialist Party could eff ectively use local politics for maintaining its territorial network of interests and cadres. Th is turned out to be obvious later on when former heads of local soviets (former Party commissars) successfully rebooted their former careers as town mayors en masse (Ellis 1997). Political contradictions of this transitional period off er an understanding of why the Hungarian path to administrative development did not prove to be a continuous success story throughout the ensuing decades (Orenstein 2008).…”
Section: Regime Change -With Limitationsmentioning
confidence: 99%
“…64 Where the communist party was formally dissolved in the transitional process, this sometimes only signaled the untrammeled continuity of dyed-inthe-wool former power-holders under a new name. In Bulgaria, the Bulgarian Socialist Party (BSP), successor party of the Communist Party formally dismantled in 1990, has remained dominant in transitional politics, 65 and in Albania, the former communist state party added insult to injury by legislating against a variety of communist and other parties, while the re-branded ruling party remained in power. Far from being directed against the former ruling communist parties, the new party bans targeted their former satellites and current rivals.…”
Section: Post-communist Party Bans: From Tragedy To Farce?mentioning
confidence: 99%